Urgensi Penetapan Peraturan Desa Tentang Keris di Desa Wisata Aeng Tong-Tong Kabupaten Sumenep - Noviana Dwi Rahmadhani (Universitas Sains dan Teknologi Komputer, 2023)
This research aims to analyze the importance of establishing regulations for the Aeng Tong-tong tourist village, Sumenep district, which are used to strive for the development and preservation of keris culture in Aeng Tong-tong village, Saronggi sub-district, Sumenep district. This research method is legal research which uses a sociological juridical approach, with observation and interviews. The results of this research show that the keris as one of the world's intangible human legacies requires a re-emphasis on the values ​​and role in society contained in the keris so that there will be no mistakes in understanding the position of the keris. The conclusion of this research is that the urgency of establishing village regulations regarding keris in the Aeng Tong Tong tourist village, Sumenep district is a form of preserving the keris cultural craft and also makes Aeng Tong Tong village the village with the highest number of keris makers in Sumenep district. The urgency of establishing this village regulation. So that there are clear legal regulations.